CGIAR Presentations at the Kick-off meeting of the Pan-African Regional Programme - Roy-Macauley, Harold; Baum, Michael; Loboguerrero Rodriguez, Ana María; Grosjean, Godefroy; Newman, Richard; Girvetz, Evan Hartunian; Rosenstock, Todd S.; Steward, Pete; Derenoncourt, Marie Ena; Wamicwe, Peter; Nowak, Andreea C.; Nangia, Vinay (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentations delivered by CGIAR scientists at the Kick-off meeting of the Pan-African Regional Green Climate Fund Readiness Programme on October 3-4, 2022 in Rabat Morocco. The presentations comprised of overall presentation of the One CGIAR, CGIAR's climate Agenda, the AICCRA project, and select CGIAR research products, science-based tools and innovations relevant to GCF proposals.